2017
DOI: 10.1111/azo.12196
|View full text |Cite
|
Sign up to set email alerts
|

The specialisation of the third metacarpal and hand in arboreal frogs: Adaptation for arboreal habitat?

Abstract: Skeletal morphology is directly associated with habitat characteristics. To investigate the arboreal adaptation, we studied the osteological morphology of the forelimbs and the third metacarpals of arboreal frogs (Rhacophoridae and Hylidae) and non-arboreal frogs (Bombinatoridae, Bufonidae, Megophryidae, Ranidae, and Microhylidae) using transparent specimens or X-rays of skeletons. Our results revealed that the bony knob on the third metacarpal, which formed by a dilated and elongated lateral articular cartila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…The secondary endochondral ossification centre in the bony knobs of Gracixalus gracilipes (see fig. in Dang et al, ) strongly support their origin as attached sesamoids (see Parsons, ).…”
Section: Sesamoids In Tetrapodamentioning
confidence: 74%
See 4 more Smart Citations
“…The secondary endochondral ossification centre in the bony knobs of Gracixalus gracilipes (see fig. in Dang et al, ) strongly support their origin as attached sesamoids (see Parsons, ).…”
Section: Sesamoids In Tetrapodamentioning
confidence: 74%
“…Sesamoids‐to‐epiphyses transformation has reported to be bidirectional (arrows 1 and 2; Bernays, ; Brunner, ; Parsons, ; Pearson & Davin, ; Vaughan & France, ; Offenbecker & Case, ; Eyal et al, ). Changes from epiphyses to apophyses (arrow 3; Parsons, ; Dang et al, ) and from sesamoids to apophyses (arrow 4; Koyama et al, ) have also been reported.…”
Section: A Dynamic Model Of the Genesis Of New Skeletal Morphologiesmentioning
confidence: 94%
See 3 more Smart Citations